Human, society, state: legal aspects in the modern world - Сопілко, Ірина Миколаївна; Череватюк, Вікторія Богданівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article examines the relation and interaction of the human, society and state at the different stages of the civilization development. The authors emphasize the importance of the discussion of these issues on the international level for quickly responding to the challenges of the modern world and the possibility to join the reforms that are taking place in Ukraine now. An important outcome of the International Conference is a scientific justification for the substantial enrichment of the constitutional and legal status of human and civil rights of Ukraine, increasing the level of realization of human rights and freedoms, reduction of human security with international standards, enhancing the formation and development of civil society in the context of the growth of its responsibility for ensuring human rights and freedoms